Comparative Genomics Suggests Mechanisms of Genetic Adaptation toward the Catabolism of the Phenylurea Herbicide Linuron in Variovorax. (2nd May 2020) - Öztürk, Başak; Werner, Johannes; Meier-Kolthoff, Jan P; Bunk, Boyke; Spröer, Cathrin; Springael, Dirk
Abstract: Biodegradation of the phenylurea herbicide linuron appears a specialization within a specific clade of the Variovorax genus. The linuron catabolic ability is likely acquired by horizontal gene transfer but the mechanisms involved are not known. The full-genome sequences of six linuron-degrading Variovorax strains isolated from geographically distant locations were analyzed to acquire insight into the mechanisms of genetic adaptation toward linuron metabolism. Whole-genome sequence analysis confirmed the phylogenetic position of the linuron degraders in a separate clade within Variovorax and indicated that they unlikely originate from a common ancestral linuron degrader. The linuron degraders differentiated from Variovorax strains that do not degrade linuron by the presence of multiple plasmids of 20–839 kb, including plasmids of unknown plasmid groups. The linuron catabolic gene clusters showed 1) high conservation and synteny and 2) strain-dependent distribution among the different plasmids. Most of them were bordered by IS 1071 elements forming composite transposon structures, often in a multimeric array configuration, appointing IS 1071 as a key element in the recruitment of linuron catabolic genes in Variovorax . Most of the strains carried at least one (catabolic) broad host range plasmid that might have been a second instrument for catabolic gene acquisition. We conclude that clade 1 Variovorax strains, despite their different geographical origin, made use of a limited genetic repertoire regarding both catabolic functions and vehicles to acquire linuron biodegradation.